Hubungan Pengetahuan dan Pelaksanaan Germas di Desa Negeri Lama Wilayah Kerja Puskesmas Passo - Lea Mediatrix Janwarin; Gracia Victoria Souisa (FORUM ILMIAH KESEHATAN, 2019)
Indonesia is currently undergoing a change in disease patterns characterized by increased deaths and morbidity due to non-communicable diseases (PTM) such as strokes, heart disease, diabetes. The Health Center Passo which is one of the health centers in Ambon City, Maluku Province shows that from January to June 2018, the number of new DM cases was 85 and hypertension was 332 people. Nearly 90% of PTM be prevented with a clean and healthy living behavior is through the Gerakan Masyarakat Hidup Sehat / GERMAS (Community Movement for Healthy Living). Germas success is highly correlated with the involvement of the whole society. Therefore, this study aimed to knowing the level of the knowledge of the community about Germas, the implementation of Germas, and the relationship of knowledge with implementation Germas in order to be a picture extent Germas as a national movement known and carried out by the people. The type of research was quantitative with cross sectional design. The population of this study was all the people of the Negeri Lama Village, with sample of research 328 respondents. Variable independent in this study was knowledge, while variable dependent in this study was the implementation of the Germas, which is physical activiy, the consumption of the vegetables and fruits, and health checks routine. Instruments research used the questionnaires and to analyzed the relationship between the knowledge and the implementation of the Germas used chi square test. The results of this research showed that there is no the relationship between the knowledge with physical activity, there is not the relationship between the knowledge with the consumption of vegetables and fruits, and there is the relationship between the knowledge with health checks routine in Negeri Lama Village 2019. The suggestion than can be given to the health center is increasing socialization about Germas to a society in the workplace and the importance of the role as well as a society in the implementation of Germas as prevention efforts non-communicable diseases. Keywords: germas; knowledge; implementation